A taxonomic review of the Old World leafhopper genus Changwhania Kwon (Hemiptera: Cicadellidae: Deltocephalinae: Paralimnini) - Zhang, Yalin; Duan, Yani; Webb, M. D. (Zootaxa, 2009)
The Old World leafhopper genus Changwhania Kwon is reviewed and three of its four species are illustrated and male genital characters are provided. One new species from China, Changwhania digitata Zhang and Duan, is described. A key to species is also provided.